Menikah Muda Pada Penduduk Di Kecamatan Sangkapura Kabupaten Gresik - Mulyani, Endah; Safriana, Rizka Esty (Universitas Muhammadiyah Gresik, 2023)
Merriage is an inner and outer bond between a man and a woman as husband and wife who re together with the aim of forming a happy family. Marriage at a young will increase various health and social problems. Sangkapura sub-district is the sub-district with the highest number of marriageables ages < 19 years in Gresik district. This study aims to look at the description of the age of marriage in the population of childearing age ini Sangkapura District. This study used a descriptive research type, the population in this study were all residents of childbearing age in Sangkapura District. The results showed that the village with the largest female population married at the age of < 19 was in the village of Kebun Teluk Dalam, which was 40,8% (206 people). The early afe of marriage causes problems in the future especially those related of reproductive health. Further research is deemed necessary to analyze the factors that influence early marriage among residents in the Sangkapura sub-district.